LINDA M. MORRA, Unarrested Archives: Case Studies in Twentieth-Century Canadian Women’s Authorship - Toews, Jennifer (Archivaria, 2016)
Unarrested Archives: Case Studies in Twentieth-Century Canadian Women’s Authorship. LINDA M. MORRA. Toronto: University of Toronto Press, 2014. ix, 244 pp. ISBN 978‑1‑4426‑2642‑3